Biomechanical aspects: Summary and consensus statements of group 4. The 5th EAO Consensus Conference 2018. (10th October 2018) - Hämmerle, Christoph H. F.; Cordaro, Luca; Alccayhuaman, Karol A. Apaza; Botticelli, Daniele; Esposito, Marco; Colomina, Lino E.; Gil, Alfonso; Gulje, Felix L.; Ioannidis, Alexis; Meijer, Henny; Papageorgiou, Spyridon N.; Raghoebar, Gerry; et al.
Abstract: Objectives: The aim of the present publication was to report on the EAO Workshop group‐4 discussions and consensus statements on the five reviews previously prepared. These reviews provided the scientific evidence on the effect of crown‐to‐implant ratio, on reconstructions with cantilevers in fully and partially edentulous patients, on biological and technical complications of tilted in comparison with straight implants, and on the effects of osseointegrated implants functioning in a residual dentition. Material and Methods: The group discussed, evaluated, corrected where deemed appropriate, and made recommendations to the authors regarding the following five reviews submitted: (a) Is there an effect of crown‐to‐implant ratio on implant treatment outcomes?; (b) Implant‐supported cantilevered fixed dental rehabilitations in fully edentulous patients; (c) and in partially edentulous patients; (d) Biological and technical complications of tilted implants in comparison with straight implants supporting fixed dental prostheses; (e) What are the adverse effects of osseointegrated implants functioning among natural teeth of a residual dentition? Based on the five manuscripts and the discussion among the group as well as the plenum members, the major findings were summarized, consensus statements were formulated, clinical recommendations were proposed, and areas of future research were identified. Results: Crown‐to‐implant ratios ranging from 0.9 to 2.2 did not influence the occurrence of biological or technical complications also in single‐tooth restorations. Reconstructions with cantilevers for the rehabilitation of fully and partially edentulous jaws showed high implant and reconstruction survival rates. In contrast, the rate of complications—in particular associated with veneering material—was high during the observation period of 5–10 years. The data reported were primarily derived from studies with high risk of bias. The data for single‐implant reconstructions were small. There was no evidence that distally tilted implants were associated with higher failure rates and increased amounts of marginal bone loss. The data supporting these findings, however, were at high risk of bias and frequently incompletely reported. Frequent positional changes occurred between the natural teeth and the implant‐supported restorations. These changes were more pronounced in younger individuals, and even though they were reduced with age, they still occurred in adult patients. Even though these changes were frequent, potential implications for the patient are unclear. Conclusions: The use of single‐tooth restorations with crown‐to‐implant ratio in between 0.9 and 2.2 may be considered a viable treatment option. Multiunit reconstructions with cantilevers are a viable treatment option in fully and partially edentulous patients. Clinicians and patients should be aware, however, that complications are frequent and primarily related to resin material used for veneering. There is some evidence that tilting an implant does affect stability of the implant and the surrounding bone. Treatment options to tilted implants should carefully be considered, as the effect on soft tissues and on prosthesis behavior is poorly reported for tilted implants. Positional changes in the dentition in relation to implant‐supported restorations occur frequently. The patient should be informed about the possible need for a treatment related to these changes in the long term.